Intelligent Traffic Lights Control by Fuzzy Logic - Khalid, Marzuki (Malaysian Journal of Computer Science, 1996)
Describes the design and implementation of an intelligent traffic lights controller based on fuzzy logic technology. A software has been developed to simulate the situation of an isolated traffic junction based on this technology. It is highly graphical in nature, uses the Windows system and allows simulation of different traffic conditions at the logic controller and a conventional fixed-time controller. Simulation results show that the fuzzy logic controller has better performance and is more cost effective.